Development of Learning Media Based on Articulate Storyline - Cahyani Hadza; Afridha Sesrita; Irman Suherman (Indonesian Journal of Applied Research (IJAR), 2020)
Utilization of technology in education will produce good quality learning, up to date, make critical thinking, have conceptual thinking and easy to access various learning resources. Together with technology, the teacher must realize a learning assisted learning media, so that students’ interest in learning increases. Articulate storyline application is an interactive multimedia application that can be used by teachers or students. Based on observations found that teachers use media objects for learning in class, especially in force material, then based on the results of interviews with teachers, teachers more often use learning media types of objects, visuals and silently projected. The purpose of this study is to validate the articulate storyline as a learning medium on force material. The steps of this research development include initial research and information gathering, planning, developing initial product formats, initial trials and product revisions. Data collected through observation, interviews and questionnaires. The results of the validation of the material experts stated that media is valid with an average value of 79.65%. Furthermore, the results of the validation of the media experts stated that media is valid with an average value of 86.16%. In tested valid media products with an average of 81.93%. From the results of these data the researchers concluded that the articulate storyline-based media are valid, and suitable for use as learning media.